2020
DOI: 10.1111/jocs.14651
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of preincisional and postincisional parasternal intercostal block on postoperative pain in cardiac surgery

Abstract: Background The optimum cardiac surgical pain management has known to maintain hemodynamic stability and, reduces respiratory and cardiovascular complications. Postoperative parasternal intercostal block has shown to reduce postoperative analgesic consumption after cardiac surgery. Therefore, this study sought to investigate the effectiveness of the preoperative ultrasound guided parasternal block in reducing postoperative pain after cardiac surgery. Methods This was a randomized, prospective, interventional, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Zhang and collaborators described on their study a significantly lower consumption of intraoperative opioids in the intervention group, that goes in hand with prior studies that have shown similar results when the block is performed after induction of anesthesia [6,7]. In a study by Padala et al, patients who received blocks pre-incision had decreased fentanyl administration intraoperatively compare to patients who received the block prior to sternotomy closure [7].…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Zhang and collaborators described on their study a significantly lower consumption of intraoperative opioids in the intervention group, that goes in hand with prior studies that have shown similar results when the block is performed after induction of anesthesia [6,7]. In a study by Padala et al, patients who received blocks pre-incision had decreased fentanyl administration intraoperatively compare to patients who received the block prior to sternotomy closure [7].…”
mentioning
confidence: 73%
“…Studies based on patient satisfaction have shown that the majority of patients continue to have mild to moderate sternotomy pain especially with movement and coughing up to post-operative day three or later [9]. Whether the block was placed post-induction or prior to sternal closure, Padala's study showed timing of placement of regional block did not seem to affect the total opioid requirement nor the pain scores for up to 24 hours postoperatively [7]. Another study by Lee and collaborators, evaluated if the administration of Liposomal Bupivacaine would prolong the analgesic effect of the regional block.…”
mentioning
confidence: 99%
“…5 Zhang et al described in their study a significantly lower consumption of intraoperative opioids in the intervention group, which goes in hand with prior studies that have shown similar results when the block is performed after induction of anesthesia. 6,7 In a study by Padala et al, 7 patients who received blocks preincision had decreased fentanyl administration intraoperatively compare to patients who received the block before sternotomy closure. In Zhang's study, the block group had faster extubation times, decreased pain scores up to 24 h after surgery, and decreased postoperative opioid administration.…”
mentioning
confidence: 99%
“…9 Whether the block was placed postinduction or before sternal closure, Padala's study showed the timing of placement of the regional block did not seem to affect the total opioid requirement nor the pain scores for up to 24 h postoperatively. 7 Another study by Lee et al, 10 evaluated if the administration of liposomal bupivacaine would prolong the analgesic effect of the regional block. This formulation of bupivacaine can have analgesic effects up to 72-96 h. In the study, the parasternal intercostal block was placed just before sternotomy closure.…”
mentioning
confidence: 99%
See 1 more Smart Citation